Gambaran Pengetahuan, Sikap, Motivasi Ibu Dan Dukungan Suami Berkaitan Dengan Pemberian Asi Eksklusif Pada Bayi Usia 6-12 Bulan - Ni Ketut Citrawati; I Dewa Gede Candra Dharma (STIKES Ngesti Waluyo, 2025)
Exclusive breastfeeding has benefits for both babies and mothers. For babies, the nutrients contained in breast milk contain bioactive components that can protect babies from infection, thereby reducing the risk of infections in children such as pneumonia, diarrhea, and intestinal diseases. The purpose of this study was to determine the knowledge, attitudes, motivation of mothers, and support of husbands related to exclusive breastfeeding in babies aged 6-12 months. The method used in this study was descriptive research with a cross-sectional approach. This study was conducted at Ganesha General Hospital from February to March 2024. The subjects in this study were 30 mothers who had infants aged 6-12 months. Data collection was carried out using purposive sampling based on inclusion and exclusion criteria. The results obtained on mothers' knowledge about exclusive breastfeeding showed that 30 respondents (100%) had good knowledge. Regarding mothers' attitudes towards exclusive breastfeeding, the majority of mothers had a fairly good attitude, namely 22 respondents (73.3%). The majority of mothers had good motivation in providing exclusive breastfeeding, namely 30 people (100%). In terms of support from husbands, 27 respondents (90%) received good support. In terms of the attitude of health workers in providing information related to exclusive breastfeeding, most respondents received a good attitude, namely 20 respondents (67%). Conclusion: The majority of mothers have good knowledge, support from their husbands, and motivation. The attitudes of mothers and health workers are considered adequate. It is hoped that the community will be able to maintain their knowledge, support from husbands, and motivation in providing exclusive breastfeeding, as well as improve the attitudes of mothers and health workers regarding exclusive breastfeeding.